2020
DOI: 10.7717/peerj.8483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid accumulation product and body mass index as indicators of diabetes diagnosis among 215,651 Chinese adults

Abstract: Purpose We aimed to assess if lipid accumulation product (LAP) could outperform body mass index (BMI) as a marker for diabetes diagnosis. Methods We analyzed the results of a national physical examination project in Urumqi, China. This project was conducted in 442 community clinics in Urumqi from October 2016 to February 2017. Results LAP was highly correlated with diabetes. The subjects with higher amounts of LAP had a higher risk of diabetes, and the prevalence of diabetes in the fourth quartile of LAP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…LAP is calculated from WC and fasting TG levels, which has a theoretical basis in reflecting the accumulation of visceral fat [ 19 ]. Several studies indicated that LAP displayed a better predictive ability in metabolic syndrome, diabetes, and impaired fasting glucose as compared with common obesity indices [ 20 22 ]. But some studies indicated that high LAP was not associated with an increased risk of T2DM [ 41 ], and LAP may not be an inexpensive tool for predicting T2DM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LAP is calculated from WC and fasting TG levels, which has a theoretical basis in reflecting the accumulation of visceral fat [ 19 ]. Several studies indicated that LAP displayed a better predictive ability in metabolic syndrome, diabetes, and impaired fasting glucose as compared with common obesity indices [ 20 22 ]. But some studies indicated that high LAP was not associated with an increased risk of T2DM [ 41 ], and LAP may not be an inexpensive tool for predicting T2DM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese cohort study indicated that the adjusted HR (95% CI) for the fourth quartile of LAP was 5.02 (2.85-8.85) in men and 6.49 (3.48-12.12) in women as compared with the first quartile [ 42 ]. A cross-sectional study of 215,651 Chinese adults found that the predictive accuracy of LAP was higher for women than for men [ 22 ]. In our study, the adjusted HR (95% CI) of T2DM in Q4 of LAP was higher for women 8.063 (5.645-11.516) than for men 6.298 (4.911-8.077) as compared with the first quartile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the identi ed cutoff value of LAP was 33.54 (sensitivity, 54.6%; speci city, 62.42%) in study population, a number of studies have found similar results. A study in northeastern Brail showed that the cutoff value of LAP index to present a higher chance of cardiovascular risk was 37.9 [49], an investigation conducted among Urumqi in China found that LAP was better than BMI to predict cardiovascular risk and the predictive accuracy was 38.41 in 215,651 adults [29]. Meanwhile, in southern Taiwan, China, Chiang et al [50] evaluated that the optimal cutoff value for the LAP index to predict diabetes was 28.4.…”
Section: Discussionmentioning
confidence: 99%
“…A family history of diabetes is considered to be an indicator of genetic susceptibility, and people with a family history of diabetes have a signi cantly higher risk than others. In addition, as IFG and diabetes are polygenic inheritance patterns, the joint in uence of risk factors may aggravate the disease [29], but there are few studies on the interaction between family history of diabetes and other risk factors. Meanwhile, hypertension is also a relatively independent risk factor for diabetes, so we performed a cross-sectional study in a large-scale population without hypertension patients to evaluate the interaction effects between family history of diabetes and LAP on IFG and diabetes, and to provide new initiatives for the prevention of IFG and diabetes.…”
Section: Introductionmentioning
confidence: 99%